Efforts to Enhance Student Activity and Enthusiasm in Islamic Religious Education (PAI) Learning with the Topic “When Life Stops” Through the Use of Discussion Methods, Group Work, and Visual Media. - Iin Hindasih; Ratna Wulan (Mentari : Journal of Islamic Primary School, 2025)
This research aims to enhance student learning activation through the use of group discussion methods. Based on data analysis and discussion of the research findings, it can be concluded that group discussions are crucial for Islamic Religious Education (PAI) learning to make it more effective and active. The problem in this study is how the implementation of discussion and Q&A learning methods, using visual media, can improve the learning activity and enthusiasm of fifth-grade students in PAI at SD Lembur Sawah, Cicantayan District, during the second semester of the 2024/2025 academic year. The objective of this research is to increase the learning activity and enthusiasm of these fifth-grade PAI students. Using a case study research type with a qualitative approach, data was obtained through interviews, observations, and documentation. Based on the research, PAI learning at SMP Negeri 3 Jombang runs smoothly, with good student grades and consistent implementation of religious programs. However, the exploration of audio-visual media in PAI learning faces obstacles due to limited facilities, necessitating the development of material visualization and adjustments to students' learning characteristics. This classroom action research consists of two cycles, with each cycle comprising the stages of planning, action implementation, observation, and reflection. Data collection techniques employed observation. The data collection tool used was an instrument in the form of an observation sheet for students during the learning process. The results of this research indicate that in Cycle I, student learning activity and enthusiasm, reflected in a fairly active learning process, were already quite good. This is evident from the data: out of 46 students, there was an increase of 10.5%, from 56.7% in the low category to 67.2%, placing them in the moderately active category for learning. Based on these data, it can be concluded that the use of discussion methods, group work, and visual media can enhance student activity and enthusiasm in learning.